PENERAPAN MODEL PEMBELAJARAN TERPADU (PENELITIAN TINDAKAN KELAS TEMA: KERAJINAN TANGAN ) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 011 KEMBANG HARUM KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Utari Indrayani; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : The Problem In this Research is that low the Result on the study of IPS.Factor that influences result of the study can be rated at about 2 group. They are: 1). The Factor from the students by they self 2) The Factor from beyond of the students. This Research talking about the use of Integrated Learning Method, the topic is : Hand made in studying IPS Secondary School. The Purpose will be find in this Research is To Know Is the Integrated Learning Method with The Topic Hand Made can be increase the result study the student class III of Secondary Scholl Number 011 Kembang Harum Subdistric of Pasir penyu Regency of Indra Giri Hulu? The Subject in this Research is students class III Secondary school Number 011 Kembang Harum in periode 2014/2015 and the Total of Students is 38 students. This Research using of 2 cycle four meeting and two Assignment.The Instrument to collecting the data is sheet observation students, The Teacher and test Assignment. This Research in form (PTK) Penelitian Tindakan Kelas, or the Research of class action.The Purpose to incresult of students IPS class III Secondary school Kembang Harum in topic buy of sale and Money. The Result of This Research can be show that the Integrated Learning Method in topic Hand Made can be increase the result of study. The result of the study can be show Raising base score by mean 57,78. At the first Assigment (1) the student score increase by mean 77,22. By mean raising 19,98 %. And the second assignment (II) score ability of the students become 84,30 %. So, the raising from base score to last score assignment II Cycle II is 27,2 %. Such was the case can be show that the application of Integrated Learning in topic : Hand Made can be increase the result study students of class III Secondary school (SD N 011) Kembang Harum Kecamatan Pasir Penyu.Keywords : Integrated Learning Method